Constraining the density dependence of the symmetry energy: the isospin transport ratio revisited. (26th November 2021) - Mallik, S; Gulminelli, F; Gruyer, D
Abstract: The isospin diffusion of the quasi-projectile formed in the Ni 64, 58 on Ni 64, 58 reactions in the Fermi energy domain is investigated in the framework of the Boltzmann–Uehling–Uhlenbeck transport model. The well known isospin transport ratio observable is revisited, with the aim of insuring an optimal comparison between experimental data and theoretical calculations and reducing the present uncertainties in the extraction of empirical equation of state parameters. We show that isospin transport ratios are sensitive to all the low order isovector parameters ( E sym, L sym and K sym, but the quantitative results depend on the choice of the isospin sensitive observable. We demonstrate that realistic models of the equation of state, covering the uncertainty that presently affects the theoretical description of neutron stars static observables, can be effectively discriminated by isospin diffusion experiments, provided the neutron to proton ratio of the projectile remnant is precisely measured as a function of centrality.